Epidemiology of norovirus disease in the first 2 years of life: A prospective multisite cohort study in Lima, Peru - Claudio F. Lanata; Giselle Soto; Ana I. Gil; Joan Neyra; Rubelio Cornejo; Candice Romero; Lucie Ecker; Maria L. Huaylinos; Sayda La Rosa; Ana Goios; Astrid Borkowski; John Weil (International Journal of Infectious Diseases)
Objectives: Norovirus is associated with 18% of acute gastroenteritis (AGE) cases worldwide. We aim to document the norovirus-related AGE incidence in peri-urban areas of Lima (Peru), evaluating the potential impact of a norovirus vaccine introduction. Methods: A prospective, community-based pediatric cohort study was established at two sites in Lima. Healthy children between 5 and 18 months were contacted weekly for AGE detection during a 6-month period. Stool samples from AGE cases were tested for norovirus by RT-PCR. Incidence and coinfection of norovirus-associated AGE were analyzed. All norovirus-positive samples were genotyped by Sanger DNA sequencing. Results: Among 498 enrolled children, 461 (93%) completed the follow-up period. We detected 799 AGE cases, yielding 676 valid stool samples. Norovirus was detected in 216 samples (32%), with an incidence of 7.7 episodes per 100 child-months (95% CI: 6.7-8.8). Genotypes GII.4 (31%) and GII.6 (22%) were frequent. Campylobacter (43%) and Salmonella spp. (15%) were the most common coinfections with norovirus. Ninety-five percent of study children had received an oral rotavirus vaccine. Conclusion: Norovirus was the second most frequent cause of AGE in this Peruvian cohort with high rotavirus vaccine coverage. An effective norovirus vaccine would have an important public health benefit in this population.